Bridging cultures, reshaping identities:: How pragmatic awareness transforms teachers in Ethiopian international schools - Deniz, Ünal (Journal of Interdisciplinary Studies in Education, 2026)
This phenomenological study explores how teachers experience intercultural pragmatic dissonances and how these experiences shape their professional identity development. In-depth interviews were conducted with 12 teachers (six Ethiopian and six international) from three international schools in Addis Ababa. Findings reveal three themes of intercultural pragmatic dissonances, cultural mediation practices, and professional identity transformation through developing pragmatic awareness. Specifically, teachers navigated pragmatic dissonances in multiple contexts by developing cultural mediation strategies, including bridge-building and fostering intercultural competence. The results illuminate how teachers progressively develop the capacity to navigate communication challenges and reconstruct their professional identities. This study reveals pragmatic awareness as a catalyst for professional transformation, demonstrating how pragmatic dissonances offer opportunities for growth.